Influence of dietary fiber levels on feed utilization and growth performance in poultry - Varastegani, Asra; Ismail, Dahlan (Global Researchers Journals, 2014)
The maintenance of poultry health is complex and relies on a delicate balance diet. Dietary fiber (DF) is a dietary component has a major influence in this regard. Utilization of fiber in the poultry diet as a supplements play an important role in poultry health as well as poultry production. Nowadays with increasing human population around the world the Utilization of natural source is a marketable point of enhancing more poultry production. DF is a heterogeneous class of components that is not hydrolyzed by the digestive enzymes of non ruminant animals, and consequently are the main substrates for bacterial fermentation in the distal part of the gut. This review presents evidence that some components of dietary fiber may improve poultry health and performance.